Strategi dalam Meningkatkan Kepuasan Anggota Penabung dengan Akad Wadi’ah di Kantor Pusat Baitul Mal Wattamwil (BMT) Sunan Drajat - Muhammad Syaichul Fatoni; Siswadi Siswadi; Risma Damayanti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
Achieving overall customer satisfaction is not easy because today's customers are increasingly educated and aware of their rights. In addition, each customer has a different level of satisfaction even though they need the same product. The process of fulfilling customer satisfaction does not only require quality products or services but also requires efforts that can increase the level of customer satisfaction. By identifying and measuring member satisfaction, several strategies can be determined to be decided next. Strategy is the steps that must be taken by a company to achieve its goals. This research was conducted at BMT Sunan Drajat Center with the aim of knowing the strategy and analyzing the supporting and inhibiting factors at BMT Sunan Drajat to increase customer satisfaction with wadi'ah contracts. BMT Sunan Drajat's strategy in increasing customer satisfaction with wadiah contracts is the absence of admin fees, the implementation of a ball pick-up system, the presence of SMS masking as a customer notification regarding transactions carried out by procuring bonuses or rewards for active customers with a mobile banking application to make it easier for customers to make transactions. The supporting and inhibiting factors experienced by BMT Sunan Drajat in an effort to increase customers with Wadi'ah contracts include the supporting factors, namely the Sunan Drajat Brand, which is of great interest to the public, strategic places that are easily accessible to customers. While the inhibiting factor is the number of customers who have become customers of BMT which existed before BMT Sunan Drajat.